Enabling International Market Linkages : Lessons and Insights - World Bank (Washington, DC, 2015)
Growth-oriented entrepreneurs, especially those in small countries and those that are highly innovative, often look to international markets to grow their business. From a development perspective, entrepreneurs successful expansion into international markets can mean revenue growth and job creation at the enterprise level, along with spillover effects into innovation, industry competitiveness, and foreign exchange on a broader economic level. However, entrepreneurs do not always have the necessary know-how and networks to expand beyond their national market, nor do they have effective resources they can draw upon to gain access to the required knowledge and contacts. InfoDev focuses on enabling the growth of early-stage enterprises across the developing world. During 2010 - 2013, infoDev piloted a few approaches to enable international market access for small, relatively early-stage, growth-oriented enterprises. In total, about 200 enterprises from more than 35 countries participated in these pilots. The results and lessons from these pilot projects summarized in this document provide insights for practitioners who are considering increasing international market access for early stage entrepreneurs. Recommendations as to further research in this field are also provided.